Impact of mortgage repayments withdrawal threat on banking stocks: An event study in China - He, Junlin; Lau, Wei-Theng; Yu, Lei; Zhu, Yunchen (SAGE Publications, 2023)
In July 2022, several media outlets reported news of Chinese homebuyers refusing to repay mortgages on unfinished buildings. It is uncertain whether this event would have had an impact on bank returns as, there is not an overwhelming amount of literature available. Therefore, we collected data from 43 A-share listed banks and the CSI 300 Index for 191 trading days. Based on the Theory of the Efficient Market Hypothesis, we used an Event Study Method to explore whether the returns of bank stocks were affected by this event. By calculating the Average Abnormal Returns and Cumulative Abnormal Returns of the samples, we found that although the withdrawal of mortgage repayments by homebuyers had a short-term significant negative impact on the returns of banks’ stocks, it was quickly absorbed by the market. We consider this may be related to the risk announcements issued by some banks. Additionally, we have provided recommendations for homebuyers, banks, and relevant institutions based on our findings.